A Rare Case of Nevus Spilus Type of Giant Congenital Melanocytic Nevus with Classic Proliferative Nodules, Intraparenchymal Melanosis, and Seizures - Pankaj Das; Biju Vasudevan; Ahmed Waheed Kashif; Lekshmi Priya Krishnan; Anand Mannu; Abhinav Kumar Verma; Shweta Pandey (Indian Journal of Paediatric Dermatology)
Congenital melanocytic nevi, as the name suggests, are present since birth. They are called giant congenital melanocytic nevus (GCMN) when the size exceeds >20 cm in diameter. Due to its unsightly appearance, there is major psychosocial impact on the patient and the family. GCMN in due course of time may give rise to malignant melanoma not only in the GCMN but also in the leptomeninges. Clinical variants of GCMN include nevus spilus type, which is a rare variant. In addition to that with time, GCMN may continue to be affected with benign nodules. We present a rare case of a nevus spilus type of GCMN with classic proliferative nodules associated with intraparenchymal melanosis in brain, leading to seizures.